Paleomagnetic evidence of the brittle deformation of the Central Patagonian Batholith at Gastre area (Chubut Province, Argentina) - Ruiz González, Víctor (2020)
Fil: Ruiz González, Víctor. Universidad de Buenos Aires. Instituto de Geociencias Básicas, Aplicadas y Ambientales de Buenos Aires. Buenos Aires, Argentina.